AN ECOLOGICAL-ECONOMIC CONVERGENCE: TRANSITION TO SUSTAINABLE ENERGY - G. Kharlamova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
Sustainable energy development is complex challenge, so only complex decisions and approaches could be possible to implement in the most efficient way. There is still open question – what is the optimal volume of new energy resources using to support sustainable development and environment safety for any state of the world. Article deals with the availability of convergence to serve for the more effective usage of analytic and system approaches for modeling ecological-economic spillovers in the case of transition to sustainable energy. The economic effects of sustainable energy transition are considered. The analysis of dynamic of energy consumption in the scale of different type of resources during 1820-2030 years depicted the situation of complicated analysis of “economy-energy-environment” linkage. It arises the agenda of necessity to implement complex approaches for modeling and forecasting of new energy systems development. Different types of models and techniques to analyze economy-energy systems are listed and compared.